Crack propagation law of rock with single fissure based on PFC2D - Yuan, Hao; Xiao, Taoli; She, Haicheng; Huang, Mei (Frontiers in Earth Science, 2023)
In the study of pre-fabricated single-fissured rock, the failure mode, mechanical properties and propagation law of rock are affected by the length and inclination angle of fissure. In this study, artificially prepared marble-like rocks with different fissure characteristics were used as rock representatives, using PFC2D software to establish a uniaxial compression model tests for rocks with fissures. The effects of different fissure lengths and inclination angles on the failure mode and crack initiation and propagation of rock-like structures were systematically studied, revealing the mechanism of macroscopic mechanical behavior of rocks containing single fissures in the process of crack initiation, propagation, and failure at the micro-level. The results show that: 1) Failure mode of the rock sample is mainly controlled by fissure inclination angle and fragmentation degree is mainly controlled by fissure length. 2) The initiation stress, damage stress, and peak stress of rock samples during loading deformation increase with the increase of fissure inclination angle, and decrease with the increase of fissure length. The crack initiation angle decreases with the increase of the fissure inclination angle. 3) Crack initiation characteristics: at a low fissure inclination angle (α< 45°), the crack initiation position has a certain offset to the center of the prefabricated fissure, or starts from the tip of the prefabricated fissure. At high fissure inclination angles (α≥45°), the crack initiates from the tip of the prefabricated fissure and forms a “dispersed” distribution. 4) The crack propagation law is mainly shear cracks, at a low fissure inclination angle (α< 45°), the crack propagation has obvious aggregation band formation. At high fissure inclination angles (α≥45°), the crack aggregation zone gradually weakened and expanded in the direction of dispersion.